The effect of general spending on the financial performance of Saudi joint-stock companies - An Empirical study on the Saudi cement sector- - Alharthy, Fatmah Mosslh; Abdulrahman, Najla Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2020)
The research aimed to measure the impact of public spending on the financial performance of cement sector companies in the Kingdom of Saudi Arabia during the period 2013- 2018, by measuring the impact of the profitability and indebtedness of the Saudi cement sector companies on government spending, both operational and capital, during the study period. The descriptive method and the content analysis were followed, as the financial statements of the companies were analyzed to test the four hypotheses related to measuring the impact of public spending on the financial performance of the Saudi cement sector companies. The results of the study showed that there is a statistically significant effect of public expenditures, both operational and capital, on the return on assets index and the total debt index on total assets. The researchers recommend the need for coordination between the Ministry of Finance and the Saudi cement sector when adjusting the amount of government spending, in order to achieve a balance between demand and supply. And work to increase government spending, which would lead to the recovery of the cement sector.